2010 ADA standards for accessible design with commentary (BNi Building News, 2012)
"This all-inclusive guide puts both the '2010 ADA standards for accessible design, ' which governs the construction and alteration of places of public use, together with the Department of Justice's 'Guidance on 2010 ADA standards for accessible design," in one complete book"--Page 4 of cover
Cover title.
Includes index.
Keywords: United States. -- Americans with Disabilities Act of 1990.; Americans with Disabilities Act of 1990 (United States); Barrier-free design -- Law and legislation -- United States.; Public buildings -- Barrier-free design -- Law and legislation -- United States.; People with disabilities -- Transportation -- Law and legislation -- United States.; Discrimination against people with disabilities -- Law and legislation -- United States.; elektronické knihy; electronic books